2015
DOI: 10.3233/jad-141824
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cognitive Reserve on Brain Functional Connectivity in Alzheimer's Disease

Abstract: One factor believed to impact brain resilience to the pathological damage of Alzheimer's disease (AD) is the so-called "cognitive reserve" (CR). A critical issue that still needs to be fully understood is the mechanism by which environmental enrichment interacts with brain plasticity to determine resilience to AD pathology. Previous work using PET suggests that increased brain connectivity might be at the origin of the compensatory mechanisms implicated in this process. This study aims to further clarify this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 34 publications
1
93
2
Order By: Relevance
“…1 Although the present study did not find statistically significant results for the aMCI group, functional connectivity disruptions within 7 and between 1,7 networks in these patients have been reported previously in the literature. Our lack of significant results for patients with aMCI could be due to the heterogeneity of the sample (early v. late aMCI), different cognitive reserve levels, which is known to influence the functional connectivity of networks, 24 or our different methodological approach. The main methodological difference between the present study and previous internetwork functional connectivity studies lies in the analysis of the correlation signal between ROIs.…”
Section: Discussionmentioning
confidence: 90%
“…1 Although the present study did not find statistically significant results for the aMCI group, functional connectivity disruptions within 7 and between 1,7 networks in these patients have been reported previously in the literature. Our lack of significant results for patients with aMCI could be due to the heterogeneity of the sample (early v. late aMCI), different cognitive reserve levels, which is known to influence the functional connectivity of networks, 24 or our different methodological approach. The main methodological difference between the present study and previous internetwork functional connectivity studies lies in the analysis of the correlation signal between ROIs.…”
Section: Discussionmentioning
confidence: 90%
“…Microstructural measures of white matter integrity such as the ones derived from Diffusion Tensor Imaging (DTI) could be useful for quantifying BR capacity as it might add important information on brain structure. Additionally, since the proposed latent model has the potential to provide longitudinal trajectories of CR, longitudinal studies should be carried out in order to investigate if CR can be a moderator of age related cognitive decline in older individuals as proposed by others [Bozzali et al, 2015; Tucker‐Drob et al, 2009]. Finally, it would be of interest to consider for other demographic characteristics (such as primary occupation) and/or cohorts characterized by high education levels to have a broader picture of the impact of FC in brain functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed several significant interaction effects between levels of CR, CSF-biomarkers (β-amyloid and tau levels), genetic AD-like phenotype (APOE status), brain atrophy and the risk to develop the clinical symptoms of AD [27,[35][36][37][38]. In particular, Jack and co-workers [35] showed that people with a high risk of cognitive impairment due to AD pathophysiological processes, have both APOE 4 and low CR levels.…”
Section: The Interaction Between Reserves and Ad-related Biomarkersmentioning
confidence: 99%
“…Bozzali and co-workers [38], by using a RoI-based RS-fMRI approach, showed that CR modulated the functional connectivity in the posterior cingulate cortex, whose disconnection with the temporal lobes is known to be critical for the conversion from MCI to AD. This effect was highly significant in AD patients, less evident in patients with MCI, and totally absent in healthy subjects [38].…”
Section: The Interaction Between Reserves and Ad-related Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation